We Were Liars: We Were Liars #1 - Lockhart, E. (New York : Delacorte Press, 2014)
Spending the summers on her family's private island off the coast of Massachusetts with her cousins and a special boy named Gat, teenaged Cadence struggles to remember what happened during her fifteenth summer.
Keywords: Love -- Fiction; Friendship -- Fiction; Families -- Fiction; Amnesia -- Fiction; Wealth -- Fiction